2015
DOI: 10.1155/2015/309042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Cystatin C as a Marker of Early Renal Impairment in Patients with Liver Cirrhosis

Abstract: Background. Serum cystatin C (CysC) was proposed as an effective reflection of the glomerular filtration rate (GFR). However, its role in patients with liver cirrhosis has not been extensively verified especially in the detection of early RI. Patients and Methods. Seventy consecutive potential candidates for living donor liver transplantation with serum creatinine (Cr) <1.5 mg/dL were included. CysC, Cr, and estimated GFR [creatinine clearance (CCr), Cockcroft-Gault formula (C-G), MDRD equations with 4 and 6 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Another study (12) used a camera-based 99m Tc-DTPA method for measuring GFR. Although the camera-based method can be useful in following patients over time, we and others have shown that this method correlates poorly with more traditional reference methods for measuring GFR (12). An additional study used urinary excretion of 99m Tc-DTPA but did not include details regarding methods to ensure complete urine collections (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study (12) used a camera-based 99m Tc-DTPA method for measuring GFR. Although the camera-based method can be useful in following patients over time, we and others have shown that this method correlates poorly with more traditional reference methods for measuring GFR (12). An additional study used urinary excretion of 99m Tc-DTPA but did not include details regarding methods to ensure complete urine collections (11).…”
Section: Discussionmentioning
confidence: 99%
“…In a limited number of studies in patients with cirrhosis, the CysC equations tend to show better results than methods based solely on SCr. However, the published performance of the equations is variable, creating uncertainty as to whether these equations may obviate the need for more accurate methods for measuring GFR in cirrhotics (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, De Souza et al evaluated over 200 patients awaiting liver transplantation and found that CysC‐based equations more precisely determined the GFR than Crea‐based equations . This was confirmed in various groups of patients with liver cirrhosis . Furthermore, previous small studies suggested CysC as a predictor for HRS and mortality .…”
mentioning
confidence: 94%
“…(23) This was confirmed in various groups of patients with liver cirrhosis. (24,25) Furthermore, previous small studies suggested CysC as a predictor for HRS and mortality. (26,27) In a small cohort of 49 patients, CysC-based estimations of GFR were predictive for overall survival.…”
mentioning
confidence: 99%